A Phase Field Approach for Martensitic Transformations and Crystal Plasticity. Issue 1 (December 2014) - Schmitt, Regina; Mayer, Patrick; Kirsch, Benjamin; Aurich, Jan; Kuhn, Charlotte; Müller, Ralf; Bhattacharya, Kaushik
Abstract This work is motivated by cryogenic turning which allows end shape machining and simultaneously attaining a hardened surface due to deformation induced martensitic transformations. To study the process on the microscale, a multivariant phase field model for martensitic transformations in conjunction with a crystal plastic material model is introduced. The evolution of microstructure is assumed to follow a time‐dependent Ginzburg‐Landau equation. To solve the field equations the finite element method is used. Time integration is performed with Euler backward schemes, on the global level for the evolution equation of the phase field, and on the element level for the crystal plastic material law. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)